Kajian Pemungut PPN Lainnya Dalam Mekanisme PMSE Atas Transaksi Digital Domestik: Proposal Untuk Indonesia - Anggita Fatmawati Putri; Suparna Wijaya (Politeknik Keuangan Negara STAN, 2022)
The purpose of this research is to examine the application of Value Trading Tax (VAT) on Trade Through Electronic Systems (PMSE) for digital transactions between customs regions in Indonesia. The research method used is descriptive qualitative with sources from the State Finance Polytechnic of STAN, the Directorate General of Taxes, and the Fiscal Policy Agency. The results show that the high number of digital ecommerce transactions in Indonesia creates potential opportunities for tax revenue. By adapting the PMSE VAT mechanism, the government can shift the VAT collection mechanism on digital transactions in Indonesia, which originally used the taxable entrepreneur mechanism (PKP) where the collector is the seller. While in PMSE, the collector is the marketplace platform as a intermediary collection. The PMSE mechanism does not require a PKP threshold to appoint the VAT collector. The implementation of this mechanism can strengthen the VAT taxation base. The PMSE VAT mechanism for Indonesia`s digital transactions will create efficiency, effectiveness and simplicity in the tax collection system. The government will also find it easier to reach the principle of neutrality and equal treatment between conventional actors and digital business actors. In addition, from the government side and platform providers, there will also be substantial benefits or incentives if this policy is successfully implemented. The government can implement a mechanism through Section 32A of Law No. 7 2021 on harmonizing tax regulations. The existence of the basis of the Law on Harmonization of Tax Regulations will create favorable conditions for the General Department of Taxation in drafting implementation documents. Tujuan penelitian adalah mengkaji penerapan Pajak Perdagangan Nilai (PPN) atas Perdagangan Melalui Sistem Elektronik (PMSE) atas transaksi digital antar daerah pabean di Indonesia. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan narasumber yang berasal dari Politeknik Keuangan Negara STAN, Direktorat Jenderal Pajak, dan Badan Kebijakan Fiskal. Hasil penelitian menunjukkan bahwa tingginya transaksi digital e-commerce di Indonesia menciptakan peluang yang potensial dalam penerimaan perpajakan. Dengan mengadaptasi mekanisme PPN PMSE, maka pemerintah dapat menggeser mekanisme pemungutan PPN atas transaksi digital di Indonesia yang semula menggunakan mekanisme pengusaha kena pajak (PKP) di mana pemungutnya merupakan penjual. Sementara dalam PMSE, maka pemungutnya adalah platform marketplace selaku intermediary collection. Mekanisme PMSE tidak membutuhkan adanya batasan PKP untuk menunjuk pemungut PPN-nya. Penerapan mekanisme ini dapat memperkuat basis pemajakan PPN. Mekanisme PPN PMSE untuk transaksi digital Indonesia akan menciptakan efisiensi, efektivitas dan kesederhanaan sistem pemungutan pajak. Pemerintah juga akan lebih mudah menggapai prinsip netralitas dan equal treatment antara pelaku konvensional dengan pelaku usaha digital. Selain itu, dari sisi pemerintah dan penyedia platform juga akan mendapat manfaat atau insentif yang cukup besar apabila kebijakan ini berhasil diterapkan. Pemerintah dapat menerapkan mekanisme tersebut melalui Pasal 32A Undang – Undang Nomor 7 Tahun 2021 tentang Harmonisasi Peraturan Perpajakan. Adanya dasar Undang–Undang Harmonisasi Peraturan Perpajakan akan memudahkan Direktorat Jenderal Pajak dalam membuat peraturan pelaksanaanya.